Effect of multi-digit tactile imagery training on reaction time - Ramu Vadivelan; Lakshminarayanan Kishor (Biomedical Human Kinetics)
Study aim: Reaction time (RT) is the time taken to make a decisive voluntary response to a stimulus. It is an indirect index of the central nervous system’s ability to process information and a simple method to evaluate sensorimotor performance and coordination. The current study explored the potential of tactile imagery (TI) training to enhance RT in distinct digits within the same hand, namely the index and middle fingers and the thumb.